2014
DOI: 10.1007/s00167-014-2847-2
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of chronic exertional compartment syndrome of the lower leg

Abstract: Case series with no comparative group, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Improvement of symptoms or satisfaction was reported by 47% (±42%) of the patients who completed a follow-up analysis, whereas 50% (±45%) returned to a form of physical activity. The well-structured gait retraining programs 20,23 and treatment with botulinum injections 22 scored highest with satisfaction rates ranging from 89% to 100%, whereas all studies with patients alone initiated modifications in activity and/or lifestyle 7,8,[24][25][26][27] scored between 0% and 84% satisfaction. Among the 171 conservatively treated patients, six cases were reported to eventually opt for surgery.…”
Section: Outcome Following Conservative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement of symptoms or satisfaction was reported by 47% (±42%) of the patients who completed a follow-up analysis, whereas 50% (±45%) returned to a form of physical activity. The well-structured gait retraining programs 20,23 and treatment with botulinum injections 22 scored highest with satisfaction rates ranging from 89% to 100%, whereas all studies with patients alone initiated modifications in activity and/or lifestyle 7,8,[24][25][26][27] scored between 0% and 84% satisfaction. Among the 171 conservatively treated patients, six cases were reported to eventually opt for surgery.…”
Section: Outcome Following Conservative Treatmentmentioning
confidence: 99%
“…ICP values were obtained both before and after surgical intervention in nine of thirty studies. Five 7,8,[28][29][30] of these found a statistically significant reduction of ICP, suggesting that surgical intervention is effective in reducing muscle compartment pressures.…”
Section: Outcome Following Surgical Treatmentmentioning
confidence: 99%
“…This cohort study compares treatment outcome as reflected by changes in cardinal symptoms, patient satisfaction, as well as return to physical activity. Similar differences in satisfaction favoring surgery were already demonstrated in most small cohorts [6,8,22,23]. However, an exact description of the methodology for determining satisfaction was often lacking.…”
Section: Discussionmentioning
confidence: 61%
“…However, a recent study showed that there is a negligible correlation between intracompartmental pressure and exertional pain experienced in the leg 1. CECS is mainly described in active athletes and military recruits, both dealing with sudden increases in the amount or intensity of activity 2–6…”
Section: Introductionmentioning
confidence: 99%
“…Without proper treatment, symptoms of CECS have shown to persist over time in a military population as long as 50 months 4. In civilian populations the definitive treatment of choice is fasciotomy, with reported success rates of 78%–98% for release of the anterior compartment.…”
Section: Introductionmentioning
confidence: 99%